Development of a system for supervised training at home with Kinect V2 - Scherer, M.; Unterbrunner, A.; Riess, B.; Kafka, P. (Procedia Engineering, 2016)
Therapy of injured professional and amateur sportsmen can take long periods of time. It is important to promote sustained motivation during long rehabilitation phases. Live feedback and playful applications enhance the compliance of users. For this project the newest version of the Microsoft Kinect sensor (Kinect v2) was used and implemented into a prototype for supervised rehabilitation of injured athletes. A playful approach combined with a proper gamification concept ensures a constant high level of motivation for athletes of all ages recovering from injuries.